Continuum‐mechanical modelling of apoptosis. Issue 1 (18th November 2019) - Schröder, Patrick; Wagner, Arndt; Stöhr, Daniela; Rehm, Markus; Ehlers, Wolfgang
Abstract: In cancer cells, the administration of drugs, such as TRAIL, can induce a mode of cell death (apoptosis). This applied reagent shifts the cell's internal inhibition and activation reactions towards the activation of caspases, triggering the cell death. In this contribution, a macroscopic model in the framework of the well‐known Theory of Porous Media is introduced to model the apoptosis reaction for lung‐cancer metastases located in brain tissue. Therein, the density‐production terms describe the apoptosis via a set of ordinary differential equations. The model is adapted to apoptosis experiments, measuring the survival rate of lung‐cancer cells in dependency of the TRAIL concentration. Thereby, the model is compared to a reduced model version using a constitutive logarithmic apoptosis function within the production terms.